Cytomegalovirus Disease in HIV-infected Children—A Single-Centre Clinical Experience over 23 Years. (26th July 2017) - Suri, Deepti; Jindal, Ankur K; Gupta, Aman; Gupta, Anju; Bajgai, Priya; Singh, Ramandeep; Singh, Mini P; Minz, Ranjana W; Arora, Sunil; Singh, Surjit
Abstract: Background: Cytomegalovirus (CMV) results in significant morbidity and mortality in Human Immunodeficiency Virus (HIV)-infected individuals. There is paucity of literature on paediatric CMV disease, especially from developing countries. Methods: A retrospective review of records of all HIV-infected children with evidence of CMV disease was done. Results: A total of 15 children were found to have CMV disease (retinitis in all, pneumonia in two and invasive gastrointestinal disease in one). Median CD4+ T cell count and percentage at diagnosis of CMV disease was 64.5 cells/µl and 3.6%, respectively. Intravenous ganciclovir was used in patients with active CMV disease. Of the 15 children, three died while two were lost to follow-up. Symptomatic patients had poor visual outcome and almost all children who were diagnosed on active screening attained normal vision. Conclusion: Retinitis is the most common CMV disease in HIV-infected children. Early detection by active screening and initiation of systemic ganciclovir reduces the morbidity.